IDDF2020-ABS-0084 Comparison of 1L adjuvant auxiliary preparations with 2l solely polyethylene glycol plus ascorbic acid regime for bowel cleaning: a meta-analysis of randomized, controlled trials. (18th November 2020) - Yuan, Xin; Zhang, Zhixin; Xie, Jiarong; Zhang, Yu; Xu, Lu; Wang, Weihong; Xu, Lei
Abstract : Background: The effectiveness of additional usage of adjuvants for bowel preparation is still unclear. This study compared 1L polyethylene glycol plus ascorbic acid with adjuvant drug regimens (1L-PEG-AA, lower-volume) with 2L polyethylene glycol plus ascorbic acid (2L-PEG-A, low-volume) to evaluate whether the adjuvants can be used to reduce the standard dosage of purgative further. Methods: The PubMed/MEDLINE, EMBASE, Cochrane Library and Web of Science database were searched up to March 2020 for randomized controlled trials (RCTs). The primary outcome was the efficacy of bowel preparation, and the secondary outcomes were patients' tolerability and complication rate. The relative risk (RR) and mean difference (MD) with 95% confidence intervals (CI) were pooled for dichotomous and continuous variables separately. The overall quality of evidence was assessed using the GRADEpro guideline development tool. Results: Five RCTs with a total of 1013 patients were included, and the majority of patients were outpatients from different hospitals. The pooled data showed no significant difference in the adequate bowel preparation rate (89.3% versus 89.4%, RR 1, 95%CI 0.95–1.05, I 2 =47%) (figure 1A ) as well as in the complication rate (RR for nausea 1.22, 95%CI 0.89–1.65, I 2 =49%; RR for bloating 0.96, 95%CI 0.73–1.28, I 2 =0%; RR for vomiting 0.69, 95%CI 0.32–1.50, I 2 =33%; RR for abdominal pain 1.01, 95%CI 0.61–1.69, I 2 =0%). But a significantly higher willingness rate was observed in the lower-volume (85.1% versus 67.9%, RR 1.25, 95%CI 1.14–1.38, I 2 =46%) (figure 1B ). The quality of primary outcome evidence was moderate. Conclusions: The findings of this meta-analysis revealed that 1L-PEG-AA might be a viable alternative to 2L-PEG-A, with comparable effectiveness, better patient preference, and no statistically significant adverse event occurrence.